Multi Criteria Decision Making Using TOPSIS Method For Choosing Mate - Palilingan, Kenneth (Universitas Sam Ratulangi, 2020)
In life, finding the ideal life partner (mate) for us is very important, because our total life also depends on the life partner (mate) we choose, for that the choice of a life partner (mate) must be done patiently, carefully and carefully. In line with that, the use of computer technology in everyday life is also increasing, one of which is the use of computers in giving the best decisions on a problem, in this case the problem of choosing the ideal life partner. In connection with the above, a decision support system is designed for the selection of an ideal prospective spouse so that users can determine the right choice of a potential partner. The method used for this Decision Support System is the Technique Order Preference by Similarity To Ideal Solution (TOPSIS) method. This method is chosen because it chooses the best alternative from an alternative, in this case the alternative in question is a prospective spouse who meets the specified criteria. The results of the process of implementing the TOPSIS method can sort the alternatives from the greatest value to the best value.